Simulation of Batch Reactive Distillation for Biodiesel Production from Oleic Acid Esterification - B. Nakkash, Nada; R. Al-Karkhi, Sarah (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
The present work concerns with simulating unsteady state equilibrium model for production of methyl oleate (biodiesel) from reaction of oleic acid with methanol using sulfuric acid as a catalyst in batch reactive distillation. MESHR equations of equilibrium model were solved using MATLAB (R2010a). The validity of simulation model was tested by comparing the simulation results with a data available in literature. UNIQUAC liquid phase activity coefficient model is the most appropriate model to describe the non-ideality of OLAC-MEOH-MEOL-H2O system. The chemical reactions rates results from EQ model indicating the rates are controlled by chemical kinetics. Several variables was studied such as molar ratio of methanol to oleic acid 4:1, 6:1 and 8:1, amount of catalyst 0.6, 1.2 and 1.8 g sulfuric acid/g oleic acid, reaction time 36, 57 and 75 minutes, and reaction temperature 100, 120 and 130oC. Taguchi method based on signal to noise ratio was used to determine the best operating conditions for biodiesel production.